UTERINE FIBROIDS: MODERN ASPECTS OF ETIOLOGY AND PATHOGENESIS (LITERATURE REVIEW) - Саяна Жаргаловна Бадмаева; Виталий Борисович Цхай; Эвелина Саркисовна Григорян; Галина Николаевна Полстяная (The Publishing House Medicine and Enlightenment, 2019)
Objective - to conduct an analytical review of modern sources of scientific literature on the pathogenesis of uterine fibroids and risk factors of its development. Materials and methods. Conducted analysis of 38 foreign and 22 domestic sources on this topic. Results. Based on the analysis of the latest scientific data, the review describes the key factors that trigger the development of uterine fibroids; presented modern theories of pathogenesis of this disease. Despite of learning a large number of researched pathogenetic mechanisms of uterine fibroids, at present there is no single clear opinion about the etiology and pathogenesis of this tumor, and many questions remain unresolved. Conclusion. Our analysis shows that uterine myoma is a multifactorial disease and can develop through various pathogenetic mechanisms, which requires further study.